2019
DOI: 10.4103/jmu.jmu_2_19
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of internal jugular vein cannulation by ultrasound-guided and anatomical landmark technique in resource-limited emergency department setting

Abstract: Background and Objectives:Central venous catheter placement is a frequently performed procedure in emergency medicine as well as critical care unit. We aimed to compare real-time ultrasonography (USG)-guided and the traditional anatomical landmark (AL) technique for the insertion of internal jugular vein (IJV) catheters in an emergency department (ED) setting.Materials and Methods:Patients requiring IJV catheterization were prospectively recruited over a period of 1 year at a single center. Cannulation was don… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 15 publications
1
6
0
3
Order By: Relevance
“…The right IJV is usually preferred because superior venacava can be reached directly from the right avoiding injuries to the ductus thoracicus. 5 It is the first choice in patients with coagulopathy. Traditionally IJV cannulation was done by palpation and using anatomical landmarks.…”
Section: Resultsmentioning
confidence: 99%
“…The right IJV is usually preferred because superior venacava can be reached directly from the right avoiding injuries to the ductus thoracicus. 5 It is the first choice in patients with coagulopathy. Traditionally IJV cannulation was done by palpation and using anatomical landmarks.…”
Section: Resultsmentioning
confidence: 99%
“…Verimli bir hemodiyaliz için travmatize edilmemiş ve komplikasyon gelişmemiş geniş bir vasküler yola ihtiyaç vardır. Yapılan birçok çalışma da İJV kateterizasyonunun USG eşliğinde yapılmasının başarılı, güvenli, kolay ve hızlı uygulanan bir yöntem olduğunu bildirilmektedir (5)(6)(7). Klasik olarak santral ven kateterizasyonu anatomik bilgi ve vene yakın arterin palpasyonu ile sağlanmaktadır.…”
Section: Discussionunclassified
“…To improve success, ultrasound has been recommended since the 1980s to guide the procedure, 4 and ultrasound‐guided IJV cannulation has shown improved success rates and significantly reduced complications 1,5 . Numerous studies have shown that the real‐time ultrasound‐guided technique significantly reduces the number of attempts to cannulate, a higher first‐pass success rate, quicker cannulation time and fewer complications compared with the conventional anatomical landmark technique 6‐9 …”
Section: Introductionmentioning
confidence: 99%
“…Various techniques for ultrasound probe position and the needle approach have been described to improve success rate and minimise complications 6‐9 . Batllori et al 10 performed a randomised comparison of three transducer orientation approaches for ultrasound‐guided IJV cannulation in 220 patients.…”
Section: Introductionmentioning
confidence: 99%